Management and development of high potential employees: a study on fifty organizations in Malaysia - Juhdi, Nurita; Pa'wan, Fatimah; Hansaram, Ram Milah@Simranpreet Kaur (2011)
The main objective of the survey was to determine the high potential (HIPO)employee development practices in Malaysia. The findings indicated that employers put high emphasis on employees who have the initiative to develop themselves, ability to consistently produce above expectation work outcomes and ability to manage changes effectively. In terms of methods used to identify HIPOs in organizations, the most common method was performance appraisal by the immediate superior and the least common method was assessment centers by internal consultants. Two most common methods to develop HIPOs were executive development programs and assignment to special projects. The majority participants reported that they faced the most common problems in HIPOs who refuse to accept geographical relocations and difficulty in removing faltering senior executives to give way to new generations. In terms of overall effectiveness of HIPO employee development programs, majority reported that the attendance rate during executive development programs were quite satisfactory. However, they indicated that when there were vacant positions at the higher level, it was quite difficult to find the replacement internally.